2022
DOI: 10.1007/s40744-022-00482-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Quantifying the Role of Inflammation in Pain Reduction for Patients With Psoriatic Arthritis Treated With Tofacitinib: A Mediation Analysis

Abstract: Introduction Pain is a multidimensional factor and core domain of psoriatic arthritis (PsA). This analysis aimed to quantify the role of potential inflammation-associated outcomes on pain reduction in patients with PsA receiving tofacitinib, using mediation modeling. Methods Pooled data were from two phase 3 studies (OPAL Broaden and OPAL Beyond) of patients with active PsA treated with tofacitinib 5 mg twice daily or placebo. Mediation modeling was utilized to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…In the tofacitinib, a Janus Kinase (JAK) inhibitor, in a phase 3 PsA trial of bio-naïve patients, known as OPAL Broaden. Mediation analysis demonstrated that 70.5% of pain reduction was through improvement of itch, enthesitis and C-reactive protein (CRP) (swollen joint count and skin score did not have weight in the model), leaving 29.5% as a direct effect of this agent [33 ▪ ]. Mediation analysis of the upadacitinib trial in biologic naive PsA patients showed that the majority of pain reduction was a direct effect versus and indirect effect on inflammation, using the surrogate measures of itch, enthesitis, and CRP as the key measures in the model for inflammation reduction [34 ▪ ].…”
Section: Mediation Analysismentioning
confidence: 99%
“…In the tofacitinib, a Janus Kinase (JAK) inhibitor, in a phase 3 PsA trial of bio-naïve patients, known as OPAL Broaden. Mediation analysis demonstrated that 70.5% of pain reduction was through improvement of itch, enthesitis and C-reactive protein (CRP) (swollen joint count and skin score did not have weight in the model), leaving 29.5% as a direct effect of this agent [33 ▪ ]. Mediation analysis of the upadacitinib trial in biologic naive PsA patients showed that the majority of pain reduction was a direct effect versus and indirect effect on inflammation, using the surrogate measures of itch, enthesitis, and CRP as the key measures in the model for inflammation reduction [34 ▪ ].…”
Section: Mediation Analysismentioning
confidence: 99%
“…Лечение ТОФА приводило к стойкому улучшению течения дактилита независимо от его локализации, с единичными случаями возникновения нового дактилита [31]. Изучение этой же когорты больных показало, что наиболее яркий эффект ТОФА отмечен в отношении кожного зуда, уровня СРБ и уменьшения признаков энтезита [32]. Показан также хороший эффект ТОФА остаточной боли [33].…”
Section: множество точек приложения тофацитинибаunclassified
“…As another example, in studying treatment effects in rheumatoid arthritis, one may aim to study the extent to which biologic therapy reduces the rate of joint damage over 2 years through a reduction of C-reactive protein (CRP). Recently, de Vlam et al 37 studied the mediating role of inflammatory markers (CRP, swollen joint count, Leeds Enthesitis Index, Psoriasis Area and Severity Index, and an itch severity score) on the causal effect of tofacitinib on pain reduction in PsA.…”
Section: Causal Effects Confounding and Selection Biasmentioning
confidence: 99%